Supply Chain Strategy for Determining Factors of Land Value Zone and Regional Tax Purpose in Medan City, Indonesia - Amalia Fachrudin, Khaira; Siahaan, Elisabet; Faisal Pane, Imam (International Journal of Supply Chain Management, 2020)
Abstract- Global supply chains have a distinct geography that involves the dimensions of production, distribution and consumption. This geography, at the heart of many sourcing strategies, is often neglected by supply chain managers, or at least scholars investigating supply chain management. The land investment has a positive impact on boosting a region's financial strength through a Rural and Urban Land and Building Tax (PBB-P2) burden. The amount of PBB-P2 payable is determined using the Sales Value of Taxable Object (SVTO) in the relevant Land Value Zone (LVZ). However, the value of SVTO is lower than and is not proportional to the land market value. This study aims to identify the land value zone and determine the factors that influencing land value zone and regional tax purposes in commercial zones with the highest SVTO in Medan, Sumatera Utara, Indonesia. This quantitative analysis tested using multiple regression and performed by Statistical Package for Social Science (SPSS-20). The result of this study showed that location has a positive and significant effect on the land value zone, while the land area has a negative and significant effect.Â  Appropriate location can save energy thereby increasing the land value zone.Â  It implies that decision-makers must consider location when determining land value zone and establishing the SVTO.